Membrane-process fractionation method for uniform tea polysaccharide
By using magnetic beads and quaternary ammonium monomers to combine small molecule adsorption particles formed by using magnetic beads and quaternary ammonium monomers during tea polysaccharide separation, and building a macroporous adsorption resin isolation layer is solved, and fast and efficient separation and uniform tea polysaccharide preparation are achieved.
Patent Information
- Application Number
- CN202411931688.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-03-25
AI Technical Summary
The prior art has problems such as long extraction time, low efficiency, large loss of active ingredients and uneven molecular weight in the separation process of tea polysaccharides. Especially in ultrafiltration membrane separation, small molecular weight polysaccharides are difficult to intercept, resulting in deletion.
The homogeneous tea polysaccharide film method is used to mix magnetic beads with quaternary ammonium salt monomers and polymerize them to form small molecule adsorption particles and combine them with macroporous resin to form an adsorption carrier in a mosaic state, and a macroporous adsorption resin isolation layer is constructed outside to separate tea polysaccharides.
It realizes rapid and efficient separation of tea polysaccharides of different molecular weights, improves the uniformity and purity of tea polysaccharides, reduces operating steps and ultrafiltration operations, and avoids the loss of small-molecular tea polysaccharides.
Smart Images

Figure CN119684485A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of tea polysaccharide extraction, and in particular to a uniform tea polysaccharide membrane fractionation separation method. Background Art
[0002] Tea polysaccharides are natural macromolecular active substances in which a large number of monosaccharides are connected to ligand proteins through glycosidic bonds. They are active complex polysaccharides different from cellulose and starch. They are mainly composed of sugars, mineral elements and protein parts, and have a relatively complex conformation. Therefore, there are great limitations on the separation of tea polysaccharides. The solubility of tea polysaccharides needs to be heated to above 85°C in water to reach 76%. High temperature reduces the activity of the protein therein, which can easily inactivate the protein. Oxidation will occur at high temperatures, making the color darker. Continued heating will cause the degradation of sugar substances, thereby reducing the sugar content. Under acidic conditions, the tea polysaccharides themselves will degrade, resulting in a decrease in the content. Therefore, there are several main methods for the extraction of tea polysaccharides, namely, the water extraction and alcohol precipitation method which is simple and inexpensive but inefficient, the acid-base extraction method with high extraction efficiency but large activity loss, the ultrasonic-microwave synergistic extraction method with fast extraction speed but partial enzymatic hydrolysis of excessive oxygen free radicals, and the supercritical fluid method which is simple to operate and pollution-free but requires high pressure.
[0003] The above purification methods all have certain defects, such as long extraction time, low extraction efficiency and large loss of effective ingredients. In addition, the use of petroleum ether for degreasing and chloroform and n-butanol solvents for protein removal in the degreasing process will lead to the loss of polysaccharide components connected by glycosidic bonds, thereby causing the loss of tea polysaccharide content. In addition, the lack of tea polysaccharides of different molecular weights in the separation process will also cause the uniformity to be destroyed.
[0004] In order to solve the defects of the above-mentioned technologies, two or more separation technologies are now often used in combination to fully utilize the advantages of each method to achieve high-purity, rapid and efficient separation and purification. Among them, the use of ultrafiltration membrane separation can relatively gently separate substances of different molecular weights, but at the same time, the ultrafiltration membrane cannot well retain small molecular weight polysaccharides, resulting in the loss of small molecular weight polysaccharides, and ultrafiltration membranes with too small pore sizes cannot effectively and quickly separate large molecular weight polysaccharides. Impurities are difficult to pass through small pores. The concentration effect of the solution may lead to the aggregation of high-concentration small molecules or large molecules, affecting the separation effect of large molecular weight polysaccharides and small molecular weight polysaccharides, and reducing the uniformity of tea polysaccharides. Summary of the invention
[0005] In order to solve the problem that the pore size of ultrafiltration membrane cannot retain tea polysaccharides of all molecular weights well for complex tea polysaccharide components, that is, it cannot remove impurities well and quickly while retaining small molecular weight tea polysaccharides, and it cannot retain small molecular weight tea polysaccharides while removing impurities quickly, the present invention provides a uniform tea polysaccharide membrane fractionation method, and the technical scheme adopted by the present invention is as follows:
[0006] S1, mixing magnetic beads and quaternary ammonium salt monomers at a solid-liquid ratio of 5-8 g:18-24 mL and adding an initiator for polymerization to obtain small molecule adsorption particles;
[0007] S2, adding small molecule adsorption particles to the preparation process of macroporous resin, wherein the mass ratio of the small molecule adsorption particles to the macroporous resin is 3-10:40-50, to form an adsorption carrier in an embedded state, and then heating and drying, and attaching a macroporous adsorption resin isolation layer to the outside of the adsorption carrier to form an adsorption retention resin;
[0008] S3, pre-treating the tea raw material and performing ultrasound-assisted extraction to obtain a crude tea polysaccharide extract, adding the adsorption and entrapment resin to the diluted crude tea polysaccharide extract, stirring and shaking for 3-6 hours to obtain a primary extract;
[0009] S4. Filter the primary extract using an ultrafiltration membrane with a molecular weight cutoff value of 50 kDa to obtain a secondary extract, rinse and filter the secondary eluate to obtain a large molecular weight polysaccharide solution and a small molecular weight loaded resin, perform alcohol analysis, centrifugation and vacuum low-temperature drying on the large molecular weight polysaccharide solution to obtain a large molecular weight uniform tea polysaccharide; then add NaCl to the small molecular weight loaded resin for elution and filtration to obtain a small molecular weight polysaccharide solution, perform alcohol analysis, centrifugation and vacuum low-temperature drying on the small molecular weight polysaccharide solution to obtain a small molecular weight uniform polysaccharide.
[0010] The present application grafts quaternary ammonium salt monomers onto the surface of magnetic beads, thereby enabling the magnetic beads to precipitate tea polysaccharides. The complex protein on the tea polysaccharides makes the polysaccharides acidic in nature, so that they can produce water-insoluble precipitates with cationic quaternary ammonium salts, thereby separating the tea polysaccharides. In order to further distinguish large-molecular-weight tea polysaccharides from small-molecular-weight tea polysaccharides, the present application mixes the magnetic beads with macroporous resins to form an adsorption carrier with a relatively uniform dispersion, so that the large-molecular-weight polysaccharides are blocked by the macroporous resin and the connection with the quaternary ammonium salt groups is reduced; and a macroporous adsorption resin isolation layer is further constructed on the outside of the adsorption carrier in an embedded state. The isolation layer can further reduce the connection between the large-molecular-weight polysaccharides and the magnetic beads on the surface of the adsorption carrier, thereby obtaining more uniform tea polysaccharides.
[0011] The present application uses ultrasound-assisted extraction during the pretreatment of tea raw materials, which not only improves the extraction efficiency of tea polysaccharides, but also sorts out the complex tea polysaccharides, thereby preliminarily separating tea polysaccharides of different molecular weights, and facilitating the purification of small molecular weight tea polysaccharides.
[0012] Preferably, the preparation method of the magnetic beads in step S1 is as follows:
[0013] FeCl 2 With FeCl 3 The solution was dissolved in distilled water to form an iron ion solution. After heating, ammonia water was added and stirred. Oleic acid was added and reacted for 2-4 hours to form surface oleic acid-modified nanoparticles. Toluene was then used as the extraction phase to extract the nanoparticles into toluene. 3-isobutylacryloxypropyltrimethoxysilane and triethylamine were then added to react. Petroleum ether was used for precipitation to obtain magnetic beads with surface modified polymerizable double bonds.
[0014] Preferably, the quaternary ammonium salt monomer in step S1 is obtained by quaternizing a halogenated hydrocarbon salt with dimethylaminoethyl methacrylate in a ratio of 1:1, the halogenated hydrocarbon is one of benzyl bromide, methyl iodide or hexyl bromide, the solvent is acetonitrile, and the inhibitor is hydroquinone.
[0015] Preferably, the initiator in step S1 is azobisisobutyronitrile.
[0016] Preferably, the preparation method of the adsorption carrier in the embedded state in step S2 is as follows:
[0017] Styrene, divinylbenzene, porogen, initiator and liquid wax are mixed in a ratio of 4-5:2:6-8:0.05-0.1:3 to obtain an oil phase, and then water and dispersant are mixed in a ratio of 200:1-5 to obtain an aqueous phase. 60-80 parts by weight of the oil phase are dropped into 100 parts by weight of the aqueous phase and the temperature is raised to 80-90°C and reacted for 4-6 hours to obtain a macroporous resin primary polymer, and then small molecule adsorption particles are added, and the reaction is continued for 6-8 hours after stirring and shaking to obtain an adsorption carrier in an embedded state.
[0018] The present application has certain restrictions on the preparation of the adsorption carrier. By controlling the above conditions and the porogen initiator, the adsorption carrier has a good pass rate for tea polysaccharides with a smaller molecular weight of 10-30kDa, thereby avoiding the precipitation of tea polysaccharides with larger molecular weight through the adsorption carrier and magnetic beads. After being affected by quaternary ammonium salts, small molecular tea polysaccharides will also be retained inside the adsorption carrier due to the barrier of the adsorption carrier, thereby facilitating separation from large molecular weight polysaccharides.
[0019] Preferably, the porogen is toluene, the initiator is benzoyl peroxide, and the dispersant is polyvinyl alcohol.
[0020] Preferably, the steps for forming the macroporous adsorption resin isolation layer in step S2 are as follows:
[0021] Styrene, divinylbenzene, porogen, initiator and liquid wax are mixed to form an oil phase, water and dispersant are used to form an aqueous phase, an adsorption carrier in an embedded state is placed in the aqueous phase, the oil phase is added dropwise to the aqueous phase and the temperature is raised to react, thereby forming a macroporous adsorption resin isolation layer on the outside of the adsorption carrier in an embedded state.
[0022] Preferably, the steps of pre-treating the tea raw material and performing ultrasound-assisted extraction in step S3 are as follows:
[0023] The tea raw material was ground, soaked in 45°C hot water for 0.5-1h, with a solid-liquid ratio of 1g:50mL, and then treated with ultrasound at a power of 250W for 1-2h to obtain a crude tea polysaccharide extract.
[0024] Preferably, the specific steps of alcohol analysis, centrifugation and vacuum low-temperature drying in step S4 are as follows:
[0025] Add ethanol in a volume 3-4 times that of the polysaccharide solution to obtain a polysaccharide precipitate, then filter the precipitate, wash the polysaccharide precipitate with anhydrous ethanol, acetone and ether in that order, and dry the washed polysaccharide precipitate in a vacuum at a low temperature of 0-5°C.
[0026] The uniform tea polysaccharide membrane fractionation separation method of the present application has a faster separation speed and better separation quality when preparing uniform tea polysaccharides.
[0027] The beneficial effects of the present invention are:
[0028] The present application uses a macroporous adsorption resin isolation layer to separate high molecular weight tea polysaccharides from low molecular weight tea polysaccharides, so that the low molecular weight tea polysaccharides are precipitated inside the adsorption retention resin, while the high molecular weight tea polysaccharides are located in the solution outside the adsorption retention resin. Tea polysaccharides of different molecular weights are homogenized by filtration and ultrafiltration membranes, which not only quickly and conveniently separates tea polysaccharides of different molecular weights, but also has fewer operating steps and does not require excessive ultrafiltration operations, thereby reducing the contact and influence between tea polysaccharides of different molecular weights, and further improving the uniformity of tea polysaccharides. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 It is a trend chart of the uniformity of polysaccharides in the examples of the present invention and the comparative examples. DETAILED DESCRIPTION
[0030] The following will refer to the attached Figure 1 The embodiments of the present invention are described in detail. It should be understood by those skilled in the art that these embodiments are only used to explain the technical principles of the present invention and are not intended to limit the protection scope of the present invention.
[0031] The tea used in this application is Jin Jun Mei black tea from Nanping, Fujian.
[0032] Preparation Example 1
[0033] Preparation of adsorption and retention resin
[0034] Preparation of magnetic beads: 2.54 g of FeCl 2 With 6.5g FeCl 3 Dissolve in 350 mL of distilled water to form an iron ion solution, heat to 66°C, add 100 mL of 25% ammonia water and stir, then slowly add 3 mL of oleic acid and react for 3 hours to form surface oleic acid-modified nanoparticles, then use an equal volume of toluene as an extraction phase and mix with the aqueous phase containing the nanoparticles to extract the nanoparticles into toluene;
[0035] Then, 20 mL of 3-isobutylacryloxypropyltrimethoxysilane and 100 mL of triethylamine were added, mixed evenly, and reacted for 30 h. 100 mL of petroleum ether was used to precipitate the magnetic beads, and after filtering, toluene and petroleum ether were used to repeatedly wash to obtain magnetic beads with surface modified polymerizable double bonds.
[0036] Preparation of quaternary ammonium salt monomer: benzyl bromide, dimethylaminoethyl methacrylate and acetonitrile were mixed in a volume ratio of 4:5:15, and 0.3% by mass of liquid phase inhibitor hydroquinone was added to carry out quaternary ammonium salt reaction for 12 hours;
[0037] Nanoparticles, quaternary ammonium salt monomers and initiator azobisisobutyronitrile were mixed at a solid-liquid ratio of 6 g: 21 mL: 0.9 g, and the temperature was raised to 60°C for polymerization reaction for 8 h to obtain small molecule adsorption particles;
[0038] Styrene, divinylbenzene, porogen toluene, initiator benzoyl peroxide and liquid wax are mixed in a mass ratio of 4.5:1.25:5:0.075:3 to obtain an oil phase, and then water and dispersant polyvinyl alcohol are mixed in a ratio of 200:3 to obtain an aqueous phase, 70 parts by weight of the oil phase are dropped into 100 parts by weight of the aqueous phase and the temperature is raised to 85°C for reaction for 5 hours to obtain a macroporous resin primary polymer, and then small molecule adsorption particles are added, and the reaction is continued for 7 hours after stirring and shaking to obtain an adsorption carrier in an embedded state. The mass ratio of the small molecule adsorption particles to the macroporous resin is 5:45 to form an embedded state. The adsorption carrier is then heated and dried until the moisture content is less than or equal to 5%. Styrene, divinylbenzene, porogen toluene, initiator benzoyl peroxide and liquid wax are mixed in a mass ratio of 4:1.5:5:0.05:3 to form an oil phase. Water and dispersant polyvinyl alcohol are formed in a ratio of 200:2 to form an aqueous phase. The embedded adsorption carrier is placed in the aqueous phase, the oil phase is dripped into the aqueous phase and heated to react. A macroporous adsorption resin isolation layer is formed on the outside of the embedded adsorption carrier. The mass of the second oil phase reaction is 25% of the mass of the first oil phase reaction. The adsorption resin is heated and dried until the moisture content is less than 5% to obtain an adsorption retention resin.
[0039] Preparation Example 2
[0040] Preparation of adsorption and retention resin
[0041] Preparation of magnetic beads: 2.68 g of FeCl 2 With 7.1 g of FeCl 3 Dissolve in 340 mL of distilled water to form an iron ion solution, heat to 66°C, add 100 mL of 25% ammonia water and stir, then slowly add 3 mL of oleic acid dropwise therein, react for 2 hours to form nanoparticles with surface oleic acid modified, then use an equal volume of toluene as an extraction phase to mix with the aqueous phase containing the nanoparticles, and extract the nanoparticles into toluene;
[0042] Then, 20 mL of 3-isobutylacryloxypropyltrimethoxysilane and 100 mL of triethylamine were added and mixed evenly, and the mixture was reacted for 30 h. The magnetic beads were precipitated with petroleum ether, filtered, and repeatedly washed with toluene and petroleum ether to obtain magnetic beads with polymerizable double bonds on the surface.
[0043] Preparation of quaternary ammonium salt monomer: methyl iodide, dimethylaminoethyl methacrylate and acetonitrile were mixed in a volume ratio of 4:5:15, and 0.3% by mass of liquid phase inhibitor hydroquinone was added to carry out quaternary ammonium salt reaction for 12 hours;
[0044] Nanoparticles, quaternary ammonium salt monomers and initiator azobisisobutyronitrile were mixed at a solid-liquid ratio of 5 g: 24 mL: 0.8 g, and the temperature was raised to 60°C for polymerization reaction for 8 h to obtain small molecule adsorption particles;
[0045] Styrene, divinylbenzene, porogen toluene, initiator benzoyl peroxide and liquid wax are mixed in a mass ratio of 4:1.5:5:0.05:3 to obtain an oil phase, and then water and dispersant polyvinyl alcohol are mixed in a ratio of 200:1 to obtain an aqueous phase. 60 parts by weight of the oil phase are dropped into 100 parts by weight of the aqueous phase and the temperature is raised to 80°C for reaction for 6 hours to obtain a macroporous resin primary polymer, and then small molecule adsorption particles are added, and the reaction is continued for 6 hours after stirring and shaking to obtain an adsorption carrier in an embedded state. The mass ratio of the small molecule adsorption particles to the macroporous resin is 3:50 to form an adsorption carrier in an embedded state. The carrier is then heated and dried until the moisture content is less than or equal to 5%. Styrene, divinylbenzene, porogen toluene, initiator benzoyl peroxide and liquid wax are mixed in a mass ratio of 5:1.5:5:0.05:3 to form an oil phase. Water and dispersant polyvinyl alcohol are formed in a ratio of 200:1 to form an aqueous phase. The embedded adsorption carrier is placed in the aqueous phase, the oil phase is dripped into the aqueous phase and the temperature is increased to react. A macroporous adsorption resin isolation layer is formed on the outside of the embedded adsorption carrier. The mass of the second oil phase reaction is 25% of the mass of the first oil phase reaction. The mixture is heated and dried until the moisture content is less than 5% to obtain an adsorption retention resin.
[0046] Preparation Example 3
[0047] Preparation of adsorption and retention resin
[0048] Preparation of magnetic beads: 2.88 g of FeCl 2 With 7.4 g of FeCl 3 Dissolve in 370 mL of distilled water to form an iron ion solution, heat to 66°C, add 100 mL of 25% ammonia water and stir, then slowly add 3 mL of oleic acid and react for 4 hours to form surface oleic acid-modified nanoparticles, then use an equal volume of toluene as an extraction phase and mix with the aqueous phase containing the nanoparticles to extract the nanoparticles into toluene;
[0049] Then, 20 mL of 3-isobutylacryloxypropyltrimethoxysilane and 100 mL of triethylamine were added and mixed evenly, and the mixture was reacted for 30 h. The magnetic beads were precipitated with petroleum ether, filtered, and repeatedly washed with toluene and petroleum ether to obtain magnetic beads with polymerizable double bonds on the surface.
[0050] Preparation of quaternary ammonium salt monomer: hexyl bromide, dimethylaminoethyl methacrylate and acetonitrile were mixed in a volume ratio of 4:5:15, and 0.3% by mass of liquid phase as a polymerization inhibitor hydroquinone was added to carry out quaternary ammonium salt reaction for 12 hours;
[0051] Nanoparticles, quaternary ammonium salt monomers and initiator azobisisobutyronitrile were mixed at a solid-liquid ratio of 8 g:18 mL:1 g, and the temperature was raised to 60°C for polymerization reaction for 8 h to obtain small molecule adsorption particles;
[0052] Styrene, divinylbenzene, porogen toluene, initiator benzoyl peroxide and liquid wax are mixed in a mass ratio of 5:1:5:0.1:3 to obtain an oil phase, and then water and dispersant polyvinyl alcohol are mixed in a ratio of 200:5 to obtain an aqueous phase, 80 parts by weight of the oil phase are dropped into 100 parts by weight of the aqueous phase, the temperature is raised to 90°C and the reaction is performed for 4 hours to obtain a macroporous resin primary polymer, and then small molecule adsorption particles are added, and the reaction is continued for 8 hours after stirring and shaking to obtain an adsorption carrier in an embedded state. The mass ratio of the small molecule adsorption particles to the macroporous resin is 10:40 to form an adsorption carrier in an embedded state. The mixture is heated and dried until the moisture content is less than or equal to 5%. Styrene, divinylbenzene, porogen toluene, initiator benzoyl peroxide and liquid wax are mixed in a mass ratio of 5:1.5:5:0.05:3 to form an oil phase. Water and dispersant polyvinyl alcohol are mixed in a ratio of 200:5 to form an aqueous phase. The embedded adsorption carrier is placed in the aqueous phase. The oil phase is added dropwise into the aqueous phase and heated to react. A macroporous adsorption resin isolation layer is formed on the outside of the embedded adsorption carrier. The mass of the second oil phase reaction is 25% of the mass of the first oil phase reaction. The mixture is heated and dried until the moisture content is less than 5% to obtain an adsorption retention resin.
[0053] Preparation Example 4: Preparation of adsorption carrier using small molecule adsorption particles instead of macroporous adsorption resin
[0054] Preparation of adsorption and retention resin
[0055] Preparation of magnetic beads: 2.54 g of FeCl 2 With 6.5g FeCl 3 Dissolve in 350 mL of distilled water to form an iron ion solution, heat to 66°C, add 100 mL of 25% ammonia water and stir, then slowly add 3 mL of oleic acid and react for 3 hours to form surface oleic acid-modified nanoparticles, then use an equal volume of toluene as an extraction phase and mix with the aqueous phase containing the nanoparticles to extract the nanoparticles into toluene;
[0056] Then, 20 mL of 3-isobutylacryloxypropyltrimethoxysilane and 100 mL of triethylamine were added, mixed evenly, and reacted for 30 h. 100 mL of petroleum ether was used to precipitate the magnetic beads, and after filtering, toluene and petroleum ether were used to repeatedly wash to obtain magnetic beads with surface modified polymerizable double bonds.
[0057] Preparation of quaternary ammonium salt monomer: benzyl bromide, dimethylaminoethyl methacrylate and acetonitrile were mixed in a volume ratio of 4:5:15, and 0.3% by mass of liquid phase inhibitor hydroquinone was added to carry out quaternary ammonium salt reaction for 12 hours;
[0058] Nanoparticles, quaternary ammonium salt monomers and initiator azobisisobutyronitrile were mixed at a solid-liquid ratio of 6 g: 21 mL: 0.9 g, and the temperature was raised to 60°C for polymerization reaction for 8 h to obtain small molecule adsorption particles;
[0059] 2 g of sodium alginate was dissolved in 100 mL of deionized water, stirred and heated to 50° C. to obtain a sodium alginate pre-liquid; 1 g of calcium chloride was dissolved in 100 mL of deionized water to obtain a 1% (w / v) calcium salt solution; small molecule adsorption particles were then added to the sodium alginate pre-liquid, and the calcium salt solution was added dropwise and slowly stirred to precipitate gel until the gel material stopped precipitating, thereby obtaining a gel adsorption carrier, which was then dried in an oven at 55° C. to obtain a sodium alginate dry adsorption carrier;
[0060] Styrene, divinylbenzene, porogen toluene, initiator benzoyl peroxide and liquid wax are mixed in a mass ratio of 4:1.5:5:0.05:3 to form an oil phase, water and dispersant polyvinyl alcohol are mixed in a ratio of 200:2 to form an aqueous phase, a sodium alginate dry adsorption carrier is placed in the aqueous phase, the oil phase is added dropwise into the aqueous phase and the temperature is raised to react, a macroporous adsorption resin isolation layer is formed on the outside of the sodium alginate dry adsorption carrier, the mass of the oil phase is 120% of the mass of the sodium alginate dry adsorption carrier, the temperature is raised and dried until the water content is less than 5%, and an adsorption retention resin is obtained.
[0061] Preparation Example 5 - No macroporous adsorption resin isolation layer was constructed
[0062] Preparation of adsorption and retention resin
[0063] The remaining steps are the same as those in Preparation Example 1, except that:
[0064] Styrene, divinylbenzene, porogen toluene, initiator benzoyl peroxide and liquid wax are mixed in a mass ratio of 4.5:1.25:5:0.075:3 to obtain an oil phase, and then water and dispersant polyvinyl alcohol are mixed in a ratio of 200:3 to obtain an aqueous phase, 70 parts by weight of the oil phase are dropped into 100 parts by weight of the aqueous phase, the temperature is raised to 85°C and the reaction is carried out for 5 hours to obtain a macroporous resin primary polymer, and then small molecule adsorption particles are added, and the reaction is continued for 7 hours after stirring and shaking to obtain an adsorption carrier in an embedded state. The mass ratio of the small molecule adsorption particles to the macroporous resin is 5:45 to form an adsorption carrier in an embedded state, and then the temperature is raised and dried to a moisture content of less than or equal to 5% to obtain an adsorption retention resin.
[0065] Preparation Example 6 - In the preparation of macroporous adsorption resin, the amount of divinylbenzene is reduced and the amount of porogen is increased
[0066] Preparation of adsorption and retention resin
[0067] The remaining steps are the same as those in Preparation Example 1, except that:
[0068] Styrene, divinylbenzene, porogen toluene, initiator benzoyl peroxide and liquid wax are mixed in a mass ratio of 4.5:0.5:8:0.075:3 to obtain an oil phase, and then water and dispersant polyvinyl alcohol are mixed in a ratio of 200:3 to obtain an aqueous phase, 70 parts by weight of the oil phase are dropped into 100 parts by weight of the aqueous phase and the temperature is raised to 85°C for reaction for 5 hours to obtain a macroporous resin primary polymer, and then small molecule adsorption particles are added, and the reaction is continued for 7 hours after stirring and shaking to obtain an adsorption carrier in an embedded state. The mass ratio of small molecule adsorption particles to macroporous resin is 5:45 to form an embedded state. The adsorption carrier is then heated and dried until the moisture content is less than or equal to 5%. Styrene, divinylbenzene, porogen toluene, initiator benzoyl peroxide and liquid wax are mixed in a mass ratio of 4:0.5:8:0.05:3 to form an oil phase. Water and dispersant polyvinyl alcohol are formed in a ratio of 200:2 to form an aqueous phase. The embedded adsorption carrier is placed in the aqueous phase, the oil phase is dripped into the aqueous phase and heated to react. A macroporous adsorption resin isolation layer is formed on the outside of the embedded adsorption carrier. The mass of the second oil phase reaction is 25% of the mass of the first oil phase reaction. The adsorption resin is heated and dried until the moisture content is less than 5% to obtain an adsorption retention resin.
[0069] Preparation Example 7 - In the preparation of macroporous adsorption resin, the amount of divinylbenzene is increased and the porogen is reduced
[0070] Preparation of adsorption and retention resin
[0071] The remaining steps are the same as those in Preparation Example 1, except that:
[0072] Styrene, divinylbenzene, porogen toluene, initiator benzoyl peroxide and liquid wax are mixed in a mass ratio of 4.5:2:3:0.075:3 to obtain an oil phase, and then water and dispersant polyvinyl alcohol are mixed in a ratio of 200:3 to obtain an aqueous phase, 70 parts by weight of the oil phase are dropped into 100 parts by weight of the aqueous phase and the temperature is raised to 85°C for reaction for 5 hours to obtain a macroporous resin primary polymer, and then small molecule adsorption particles are added, and the reaction is continued for 7 hours after stirring and shaking to obtain an adsorption carrier in an embedded state. The mass ratio of the small molecule adsorption particles to the macroporous resin is 5:45 to form an embedded state. The adsorption carrier is then heated and dried until the moisture content is less than or equal to 5%. Styrene, divinylbenzene, porogen toluene, initiator benzoyl peroxide and liquid wax are mixed in a mass ratio of 4:2:3:0.05:3 to form an oil phase. Water and dispersant polyvinyl alcohol are formed in a ratio of 200:2 to form an aqueous phase. The embedded adsorption carrier is placed in the aqueous phase, the oil phase is dripped into the aqueous phase and heated to react. A macroporous adsorption resin isolation layer is formed on the outside of the embedded adsorption carrier. The mass of the second oil phase reaction is 25% of the mass of the first oil phase reaction. The adsorption resin is heated and dried until the moisture content is less than 5% to obtain an adsorption retention resin.
[0073] Example 1
[0074] The tea raw material was ground and soaked in hot water at 45°C for 0.8h, with a solid-liquid ratio of 1g:50mL, and then treated with ultrasound at a power of 250W for 1.5h to obtain a crude tea polysaccharide extract. The adsorption and retention resin in Preparation Example 1 and the diluted crude tea polysaccharide extract were mixed at a solid-liquid ratio of 11g:100mL, and stirred and shaken for 5h to obtain a primary extract. The primary extract was filtered using an ultrafiltration membrane with a molecular weight cutoff value of 50kDa to obtain a secondary extract after removing substances that can pass through the ultrafiltration membrane. The secondary eluate was rinsed and filtered using deionized water to obtain a macromolecular polysaccharide solution and a small molecule loaded resin.
[0075] Add ethanol with a volume three times that of the polysaccharide solution to obtain a polysaccharide precipitate, then filter the precipitate, wash the polysaccharide precipitate with anhydrous ethanol, acetone and ether in that order, and dry the washed polysaccharide precipitate in a vacuum at a low temperature of 3°C to obtain a high molecular weight uniform tea polysaccharide;
[0076] A NaCl solution with a concentration of 0.2 mol / L is added to the small molecule loaded resin for elution and filtration, and the amount of sodium chloride used is 9 times the mass of the small molecule loaded resin to obtain a small molecule polysaccharide solution. Ethanol with a volume 3 times that of the polysaccharide solution is added to the small molecule polysaccharide solution to obtain a polysaccharide precipitate, which is then filtered and washed with anhydrous ethanol, acetone and ether in that order. The washed polysaccharide precipitate is placed in a vacuum and dried at a low temperature at 3°C to obtain a small molecular weight uniform polysaccharide.
[0077] Example 2
[0078] The tea raw material was ground and soaked in hot water at 45°C for 0.8h, with a solid-liquid ratio of 1g:50mL, and then treated with ultrasound at a power of 250W for 1.5h to obtain a crude tea polysaccharide extract. The adsorption and retention resin in Preparation Example 2 and the diluted crude tea polysaccharide extract were mixed at a solid-liquid ratio of 10g:100mL, and stirred and shaken for 3h to obtain a primary extract. The primary extract was filtered using an ultrafiltration membrane with a molecular weight cutoff value of 50kDa to remove substances that can pass through the ultrafiltration membrane to obtain a secondary extract. The secondary eluate was rinsed and filtered with deionized water to obtain a macromolecular polysaccharide solution and a small molecule loaded resin.
[0079] Add ethanol with a volume 4 times that of the polysaccharide solution to obtain a polysaccharide precipitate, then filter the precipitate, wash the polysaccharide precipitate with anhydrous ethanol, acetone and ether in that order, and dry the washed polysaccharide precipitate in a vacuum at a low temperature of 0°C to obtain a high molecular weight uniform tea polysaccharide;
[0080] A NaCl solution with a concentration of 0.2 mol / L is added to the small molecule loaded resin for elution and filtration, and the amount of sodium chloride used is 8 times the mass of the small molecule loaded resin to obtain a small molecule polysaccharide solution. Ethanol with a volume 4 times that of the polysaccharide solution is added to the small molecule polysaccharide solution to obtain a polysaccharide precipitate, which is then filtered and washed with anhydrous ethanol, acetone and ether in that order. The washed polysaccharide precipitate is placed in a vacuum and dried at a low temperature at 0°C to obtain a small molecular weight uniform polysaccharide.
[0081] Example 3
[0082] The tea raw material was ground and soaked in hot water at 45°C for 0.8h, with a solid-liquid ratio of 1g:50mL, and then treated with ultrasound at a power of 250W for 1.5h to obtain a crude tea polysaccharide extract. The adsorption and retention resin in Preparation Example 3 and the diluted crude tea polysaccharide extract were mixed at a solid-liquid ratio of 12g:100mL, and stirred and shaken for 6h to obtain a primary extract. The primary extract was filtered using an ultrafiltration membrane with a molecular weight cutoff value of 50kDa to remove substances that can pass through the ultrafiltration membrane to obtain a secondary extract. The secondary eluate was rinsed and filtered with deionized water to obtain a macromolecular polysaccharide solution and a small molecule loaded resin.
[0083] Add ethanol with a volume three times that of the polysaccharide solution to obtain a polysaccharide precipitate, then filter the precipitate, wash the polysaccharide precipitate with anhydrous ethanol, acetone and ether in that order, and dry the washed polysaccharide precipitate in a vacuum at a low temperature of 5°C to obtain a high molecular weight uniform tea polysaccharide;
[0084] A NaCl solution with a concentration of 0.2 mol / L is added to the small molecule loaded resin for elution and filtration, and the amount of sodium chloride used is 10 times the mass of the small molecule loaded resin to obtain a small molecule polysaccharide solution. Ethanol with a volume 3 times that of the polysaccharide solution is added to the small molecule polysaccharide solution to obtain a polysaccharide precipitate, which is then filtered and washed with anhydrous ethanol, acetone and ether in that order. The washed polysaccharide precipitate is placed in a vacuum and dried at a low temperature at 5°C to obtain a small molecular weight uniform polysaccharide.
[0085] Comparative Example 1
[0086] In this example, the adsorption and interception resin of Preparation Example 4 was used to mix the crude tea polysaccharide extract, and the remaining steps were the same as those of Example 1.
[0087] Comparative Example 2
[0088] In this example, the adsorption and interception resin of Preparation Example 5 was used to mix the crude tea polysaccharide extract, and the remaining steps were the same as those of Example 1.
[0089] Comparative Example 3
[0090] In this example, the adsorption and interception resin of Preparation Example 6 was used to mix the crude tea polysaccharide extract, and the remaining steps were the same as those of Example 1.
[0091] Comparative Example 4
[0092] In this example, the adsorption and interception resin of Preparation Example 7 was used to mix the crude tea polysaccharide extract, and the remaining steps were the same as those of Example 1.
[0093] Experiments and data
[0094] The high molecular weight tea polysaccharides and low molecular weight tea polysaccharides extracted from the above-mentioned embodiments and comparative examples were tested for the content of low molecular weight polysaccharides and high molecular weight polysaccharides to compare their uniformity. The testing method is as follows:
[0095] Firstly, the total content of tea polysaccharides in the tea polysaccharide crude extract was tested;
[0096] Reagents: 1.5% (w / v) phenol solution, 0.5 g phenol dissolved in 100 mL distilled water; 98% concentrated sulfuric acid.
[0097] Prepare a series of glucose solutions with known concentrations (e.g. 0, 10, 20, 30, 40, 50 μg / mL)
[0098] The crude extracts of tea polysaccharides were dissolved in distilled water respectively.
[0099] Add glucose solution and the uniform tea polysaccharide solution to be tested into a test tube, and add equal volumes of concentrated sulfuric acid respectively, and then add 10% volume fraction of phenol solution, and heat in a 40°C water bath for 10 minutes.
[0100] The absorbance of each test tube at a wavelength of 490 nm, i.e., the OD value, was measured using a spectrophotometer, and the tea polysaccharide content in the tea polysaccharide crude extract was found to be approximately 28.32 mg / g-34.83 mg / g.
[0101] Then, the molecular weight distribution of the tea polysaccharides in each embodiment and comparative example is measured by gel permeation chromatography to obtain the uniformity of the molecular weight of the tea polysaccharides;
[0102] Uniformity of small molecule polysaccharides: the proportion of small molecule tea polysaccharides in the total measured polysaccharides
[0103] Uniformity of macromolecular polysaccharides: the proportion of macromolecular tea polysaccharides in the total measured polysaccharides
[0104] The test results are shown in Table 1 below:
[0105]
[0106] The content of small molecular weight polysaccharides in Comparative Examples 1 and 4 is too small to calculate the proportion, and a line graph is drawn for the uniformity of small molecular weight polysaccharides and large molecular weight polysaccharides, as shown in FIG. Figure 1 shown.
[0107] analyze
[0108] From the data in Table 1 of Examples 1 to 3, it can be seen that the molecular weight uniformity of the small molecule tea polysaccharides and the large molecule tea polysaccharides in the examples of the present application is good, the degree of separation between the large molecule polysaccharides and the small molecule polysaccharides is good, and the loss of the small molecule polysaccharides is extremely small.
[0109] From the data of Comparative Example 1 in Table 1, it can be seen that Comparative Example 1 did not use macroporous adsorption resin and small molecule adsorption particles for mixed dispersion, but used sodium alginate-coated magnetic beads. Therefore, the loss of small molecule polysaccharides in Comparative Example 1 was relatively large, and only a large amount of high molecular weight tea polysaccharides were obtained, indicating that the use of macroporous adsorption resin allows small molecule polysaccharides to be retained without loss.
[0110] From the data of Comparative Example 2 in Table 1, it can be seen that Comparative Example 2 did not construct a macroporous adsorption resin isolation layer, the uniformity of small molecule polysaccharides in Comparative Example 2 was low, and the proportion of small molecule polysaccharides significantly exceeded the normal content. It can be concluded that the small molecule polysaccharides contain too much macromolecule polysaccharides, which proves that the construction of a macroporous adsorption resin isolation layer can effectively prevent macromolecule polysaccharides from mixing into small molecule polysaccharides, and effectively improve the uniformity of small molecule polysaccharides.
[0111] It can be seen from the experimental data of Comparative Example 3 in Table 1 that when preparing the macroporous adsorption resin, Comparative Example 3 reduced the amount of divinylbenzene and increased the amount of porogen, which resulted in the pore size of the macroporous adsorption resin being too large, and the uniformity of the small molecule polysaccharides in Comparative Example 3 was extremely low, and the proportion of small molecule polysaccharides also significantly exceeded the normal content, which can prove that the excessively large pores of the macroporous adsorption resin will cause the large molecular weight adsorption resin to react with the quaternary ammonium salt on the surface of the magnetic beads, thereby reducing the uniformity of the small molecule polysaccharides.
[0112] It can be seen from the experimental data of Comparative Example 4 in Table 1 that when preparing the macroporous adsorption resin, the amount of divinylbenzene was increased and the amount of porogen was reduced, which resulted in the macroporous adsorption resin being too highly cross-linked and the pore size being too small. As a result, the small molecular weight tea polysaccharides in Comparative Example 4 were unable to effectively contact and react with the magnetic beads, proving that only suitable macroporous resins can effectively retain the content of small molecular weight tea polysaccharides without causing the loss of small molecular weight polysaccharides.
[0113] So far, the technical solutions of the present invention have been described in conjunction with the preferred embodiments shown in the accompanying drawings. However, it is easy for those skilled in the art to understand that the protection scope of the present invention is obviously not limited to these specific embodiments. Without departing from the principle of the present invention, those skilled in the art can make equivalent changes or substitutions to the relevant technical features, and the technical solutions after these changes or substitutions will fall within the protection scope of the present invention.
Claims
1. A uniform tea polysaccharide membrane fractionation method, characterized in that: The specific steps include: S1, mixing magnetic beads and quaternary ammonium salt monomers at a solid-liquid ratio of 5-8 g:18-24 mL and adding an initiator for polymerization to obtain small molecule adsorption particles; S2, adding small molecule adsorption particles to the preparation process of macroporous resin, wherein the mass ratio of the small molecule adsorption particles to the macroporous resin is 3-10:40-50, to form an adsorption carrier in an embedded state, and then heating and drying, and attaching a macroporous adsorption resin isolation layer to the outside of the adsorption carrier to form an adsorption retention resin; S3, pre-treating the tea raw material and performing ultrasound-assisted extraction to obtain a crude tea polysaccharide extract, adding the adsorption and entrapment resin to the diluted crude tea polysaccharide extract, stirring and shaking for 3-6 hours to obtain a primary extract; S4. Filter the primary extract using an ultrafiltration membrane with a molecular weight cutoff value of 50 kDa to obtain a secondary extract, rinse and filter the secondary eluate to obtain a large molecular weight polysaccharide solution and a small molecular weight loaded resin, perform alcohol analysis, centrifugation and vacuum low-temperature drying on the large molecular weight polysaccharide solution to obtain a large molecular weight uniform tea polysaccharide; then add NaCl to the small molecular weight loaded resin for elution and filtration to obtain a small molecular weight polysaccharide solution, perform alcohol analysis, centrifugation and vacuum low-temperature drying on the small molecular weight polysaccharide solution to obtain a small molecular weight uniform polysaccharide.
2. A uniform tea polysaccharide membrane fractionation method according to claim 1, characterized in that: The preparation method of the magnetic beads in step S1 is as follows: FeCl2 and FeCl3 are dissolved in distilled water to form an iron ion solution. After heating, ammonia water is added and stirred. Oleic acid is added and reacted for 2-4 hours to form surface oleic acid-modified nanoparticles. Toluene is then used as an extraction phase to extract the nanoparticles into toluene. 3-isobutylacryloxypropyltrimethoxysilane and triethylamine are then added to react and petroleum ether is used for precipitation to obtain magnetic beads with surface modified polymerizable double bonds.
3. A uniform tea polysaccharide membrane fractionation method according to claim 1, characterized in that: The quaternary ammonium salt monomer in step S1 is obtained by quaternizing a halogenated hydrocarbon salt with dimethylaminoethyl methacrylate in a ratio of 1:1, the halogenated hydrocarbon is one of benzyl bromide, methyl iodide or hexyl bromide, the solvent is acetonitrile, and the inhibitor is hydroquinone.
4. A uniform tea polysaccharide membrane fractionation method according to claim 1, characterized in that: The initiator in step S1 is azobisisobutyronitrile.
5. The uniform tea polysaccharide membrane fractionation method according to claim 1, characterized in that: The preparation method of the adsorption carrier in the embedded state in step S2 is as follows: Styrene, divinylbenzene, porogen, initiator and liquid wax are mixed in a ratio of 4-5:2:6-8:0.05-0.1:3 to obtain an oil phase, and then water and dispersant are mixed in a ratio of 200:1-5 to obtain an aqueous phase. 60-80 parts by weight of the oil phase are dropped into 100 parts by weight of the aqueous phase and the temperature is raised to 80-90°C and reacted for 4-6 hours to obtain a macroporous resin primary polymer, and then small molecule adsorption particles are added, and the reaction is continued for 6-8 hours after stirring and shaking to obtain an adsorption carrier in an embedded state.
6. A uniform tea polysaccharide membrane fractionation method according to claim 5, characterized in that: The porogen is toluene, the initiator is benzoyl peroxide, and the dispersant is polyvinyl alcohol.
7. The uniform tea polysaccharide membrane fractionation method according to claim 1, characterized in that: The steps for forming the macroporous adsorption resin isolation layer in step S2 are as follows: Styrene, divinylbenzene, porogen, initiator and liquid wax are mixed to form an oil phase, water and dispersant are used to form an aqueous phase, an adsorption carrier in an embedded state is placed in the aqueous phase, the oil phase is added dropwise to the aqueous phase and the temperature is raised to react, thereby forming a macroporous adsorption resin isolation layer on the outside of the adsorption carrier in an embedded state.
8. The uniform tea polysaccharide membrane fractionation method according to claim 1, characterized in that: The steps of pre-treatment and ultrasound-assisted extraction of the tea raw material in step S3 are as follows: The tea raw material was ground, soaked in 45°C hot water for 0.5-1h, with a solid-liquid ratio of 1g:50mL, and then treated with ultrasound at a power of 250W for 1-2h to obtain a crude tea polysaccharide extract.
9. A uniform tea polysaccharide membrane fractionation method according to claim 1, characterized in that: The specific steps of alcohol separation, centrifugation and vacuum low-temperature drying in step S4 are as follows: Add ethanol in a volume 3-4 times that of the polysaccharide solution to obtain a polysaccharide precipitate, then filter the precipitate, wash the polysaccharide precipitate with anhydrous ethanol, acetone and ether in that order, and dry the washed polysaccharide precipitate in a vacuum at a low temperature of 0-5°C.
10. Use of the uniform tea polysaccharide membrane fractionation method according to any one of claims 1 to 9 in preparing uniform tea polysaccharides.